Gejala Hipoksia dan Barotrauma dalam Ruang Udara Bertekanan Rendah pada Awak Pesawat Lakespra dr. Saryanto - Putri Avrilia Nurma Irani; Pritha Maya Savitri; Riezky Valentina Astari; Nurfitri Bustamam (HB PRESS, 2025)
In carrying out their duties, military aircrew must be able to adapt to an environment where the higher the location from sea level, the barometric pressure will decrease. This decrease in pressure leads to the occurrence of hypoxia. Hypoxia is a condition of lack of oxygen due to decrease in atmospheric oxygen pressure so that ventilation-perfusion disturbances occur. In addition to causing hypoxia, changes in barometric pressure give rise to several gas changes in the body, one of which is barotrauma. The fatal conditions due to changes in barometric pressure can be prevented through hypobaric chamber training at 25.000 feet. This study aims to determine the description of hypoxia symptoms and barotrauma in military aircrew at Lakespra dr. Saryanto. The design of the study was descriptive with data derived from 97 out of 147 the medical records of military aircrews with simple random sampling. The result showed that 16 people (16,5%) experienced cognitive symptoms, 7 people (7,2%) experienced psychomotor symptoms, 21 people (21,6%) experienced visual symptoms, and 61 people (62,9%) experienced non-specific symptoms.